2009
DOI: 10.1073/pnas.0912101106
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the catalytically inactive kinase domain of the human EGF receptor 3

Abstract: The kinase domain of human epidermal growth factor receptor (HER) 3/ErbB3, a member of the EGF receptor (EGFR) family, lacks several residues that are critical for catalysis. Because catalytic activity in EGFR family members is switched on by an allosteric interaction between kinase domains in an asymmetric kinase domain dimer, HER3 might be specialized to serve as an activator of other EGFR family members. We have determined the crystal structure of the HER3 kinase domain and show that it appears to be locked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
317
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(338 citation statements)
references
References 42 publications
20
317
0
1
Order By: Relevance
“…However, structural differences in the N lobe-including the shortened αC-helix-reinforce the argument that ErbB3-TKD cannot be activated (as "receiver") by the same types of interactions thought to activate EGFR, ErbB4, and ErbB2 in heterodimeric complexes. Jura et al (30) very recently reported an ErbB3-TKD 674-1001 structure [Protein Data Bank (PDB) ID 3KEX] that is essentially identical to that reported here and have confirmed the ability of ErbB3-TKD 674-1001 to function as an allosteric activator of EGFR-TKD in vitro. If the ErbB3-TKD does function as a receiver kinase in ErbB receptor dimers, it must do so through N-lobe interactions distinct from those described for EGFR (5) and ErbB4 (27).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…However, structural differences in the N lobe-including the shortened αC-helix-reinforce the argument that ErbB3-TKD cannot be activated (as "receiver") by the same types of interactions thought to activate EGFR, ErbB4, and ErbB2 in heterodimeric complexes. Jura et al (30) very recently reported an ErbB3-TKD 674-1001 structure [Protein Data Bank (PDB) ID 3KEX] that is essentially identical to that reported here and have confirmed the ability of ErbB3-TKD 674-1001 to function as an allosteric activator of EGFR-TKD in vitro. If the ErbB3-TKD does function as a receiver kinase in ErbB receptor dimers, it must do so through N-lobe interactions distinct from those described for EGFR (5) and ErbB4 (27).…”
Section: Resultssupporting
confidence: 54%
“…QM/MM simulations also argue that the inactive-like ErbB3-TKD crystal structure presented here and recently by Jura et al (30) can catalyze phosphoryl transfer. Thus, ErbB3 does appear to have an active tyrosine kinase in its intracellular domain.…”
Section: Discussionmentioning
confidence: 85%
“…Structural modeling of the intracellular kinase domain region based on a published HER3 kinase model did not reveal major structural differences between wild type HER3, HER3-2-3, and HER3-2-2 (Jura et al, 2009b;Jura et al, 2009a) (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
“…HER3 is different from EGFR, HER2 and HER4 in that it lacks intrinsic kinase activity and has not been reported to form homodimers on cell surface (Sierke et al, 1997;Berger et al, 2004). Since the catalytically inactive kinase domain of HER3 is not capable of activating the kinase domain of its partnering receptors, HER3 is suggested to have evolved as a dedicated and specialized activating receptor in the EGFR family (Jura et al, 2009a;Amin et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation